Mouth rinses efficacy on salivary SARS‐CoV‐2 viral load: A randomized clinical trial - Alzahrani, Manar M.; Bamashmous, Shatha; Alkharobi, Hanaa; Alghamdi, Abdullah; Alharbi, Rahaf H.; Hassan, Ahmed M.; Darwish, Manar; Bukhari, Abdullah; Mahmoud, Ahmad Bakur; Alfaleh, Mohamed A.; Mirza, Ahmed A.; Abuzenadah, Adel M.; et al. (Journal of medical virology, 2023)
Considering the global trend to confine the COVID‐19 pandemic by applying various preventive health measures, preprocedural mouth rinsing has been proposed to mitigate the transmission risk of SARS‐CoV‐2 in dental clinics. The study aimed to investigate the effect of different mouth rinses on salivary viral load in COVID‐19 patients. This study was a single‐center, randomized, double‐blind, six‐parallel‐group, placebo‐controlled clinical trial that investigated the effect of four mouth rinses (1% povidone‐iodine, 1.5% hydrogen peroxide, 0.075% cetylpyridinium chloride, and 80 ppm hypochlorous acid) on salivary SARS‐CoV‐2 viral load relative to the distilled water and no‐rinse control groups. The viral load was measured by quantitative reverse transcription PCR (RT‐qPCR) at baseline and 5, 30, and 60 min post rinsing. The viral load pattern within each mouth rinse group showed a reduction overtime; however, this reduction was only statistically significant in the hydrogen peroxide group. Further, a significant reduction in the viral load was observed between povidone‐iodine, hydrogen peroxide, and cetylpyridinium chloride compared to the no‐rinse group at 60 min, indicating their late antiviral potential. Interestingly, a similar statistically significant reduction was also observed in the distilled water control group compared to the no‐rinse group at 60 min, proposing mechanical washing of the viral particles through the rinsing procedure. Therefore, results suggest using preprocedural mouth rinses, particularly hydrogen peroxide, as a risk‐mitigation step before dental procedures, along with strict adherence to other infection control measures.